Proceedings of ArcheoFOSS : free, libre and open source software e open format nei processi di ricerca archeologica : VIII Edizione, Catania 2013 - Stanco, Filippo,; Gallo, Giovanni, 1962- (Archaeopress, 2016)
The eighth ArcheoFOSS workshop was held in Catania at the Department of Mathematics and Informatics of Catania University in June 2013. The workshop was attended by about 60 Italian scientists and specialists of open source technology for cultural heritage and archaeology. This book provides readers and experts with useful ideas and research perspectives addressed by the workshop.